The relationship between online risk exposure and depression among college students: the multiple mediating effects of emotional security and Suppress Happiness - Wang, Haihong; Zhang, Shang; Feng, Xiaoxia; Jiang, Lan; Li, Jinglin; Gong, Yuhong; Jiang, Zihan; Yi, Xinfa (Frontiers in Psychology, 2025)
BackgroundThe relationship between online risk exposure and depression among college students has aroused great attention in academic and educational circles. This study constructs a structural equation model to examine the role of emotional security and Suppress Happiness in the relationship between online risk exposure and depression among college students.MethodsA total of 986 Chinese college students (M = 19.74 years old, 64.6% female) participated in an online survey on online risk exposure scale, emotional security questionnaire, Suppress Happiness scale and depression scale. Descriptive analysis, correlation analysis, stepwise regression analysis, and structural equation modeling analysis were performed on the collected data.ResultsOnline risk exposure positively correlates with suppressed happiness and depression, but negatively with emotional security. Emotional security, in turn, negatively relates to suppressed happiness and depression. Emotional security (standardized indirect effect = 0.030, 95% CI: 0.011–0.064) and Suppress Happiness (standardized indirect effect = 0.112, 95% CI: 0.082–0.154) mediated the relationship between online risk exposure and depression, and they (standardized indirect effect = 0.008, 95% CI: 0.003–0.018) also had a serial mediating effect.ConclusionOnline risk exposure can not only directly trigger depression among college students, but also indirectly induce depression by enhancing emotional insecurity and Suppress Happiness, along with their chain-mediated effects. This study provides the theoretical basis and practical guidance for college students in the Internet era to reduce online risk exposure, prevent and treat depression.